C♯ game programming cookbook for Unity 3D / Jeff W Murray - Murray, Jeff W.
"This book supplies a hands-on approach suitable for creating video games with the Unity game engine. The author's approachable writing style provides a solid base for experienced C♯ programmers to be able to make games with Unity3d and presents readers with a set of recipes for scripting components such as game logic controllers, input management scripts, and character and animation control scripts. The final part of the book provides recipes for actual, playable example games made up of the code recipes from earlier chapters"--